15-Deoxy-Δ12,14-prostaglandin J2 Exerts Antioxidant Effects While Exacerbating Inflammation in Mice Subjected to Ureteral Obstruction - Line Nilsson; Fredrik Palm; Rikke Nørregaard (Hindawi Limited, 2017)
Urinary obstruction is associated with inflammation and oxidative stress, leading to renal dysfunction. Previous studies have shown that 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) has both antioxidant and anti-inflammatory effects. Using a unilateral ureteral obstruction (UUO) mouse model, we examined the effects of 15d-PGJ2 on oxidative stress and inflammation in the kidney. Mice were subjected to UUO for 3 days and treated with 15d-PGJ2. Protein and RNA expression were examined using immunoblotting and qPCR. 15d-PGJ2 increased NF-E2-related nuclear factor erythroid-2 (Nrf2) protein expression in response to UUO, and heme oxygenase 1 (HO-1), a downstream target of Nrf2, was induced by 15d-PGJ2. Additionally, 15d-PGJ2 prevented protein carbonylation, a UUO-induced oxidative stress marker. Inflammation, measured by nuclear NF-κB, F4/80, and MCP-1, was increased in response to UUO and further increased by 15d-PGJ2. Renal injury was aggravated by 15d-PGJ2 treatment as measured by kidney injury molecule-1 (KIM-1) and cortical caspase 3 content. No effect of 15d-PGJ2 was observed on renal function in mice subjected to UUO. This study illustrates differentiated functioning of 15d-PGJ2 on inflammation and oxidative stress in response to obstructive nephropathy. High concentrations of 15d-PGJ2 protects against oxidative stress during 3-day UUO in mice; however, it aggravates the associated inflammation.